(untitled) (Universal International Scientific Journal, 2026)
This article highlights the importance of building immunity to information attacks in adolescent psychology. It is argued that television, audio, multimedia products, and Internet tools that have entered the lives of adolescents exert pressure on the mental and psycho-emotional state of children and young people and control them. The role and tasks of the family in such situations are analyzed.